2020
DOI: 10.3390/vaccines8010119
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination in Italian Healthcare Workers (2018–2019 Season): Strengths and Weaknesses. Results of a Cohort Study in Two Large Italian Hospitals

Abstract: Background: Annual vaccination is the most effective way to combat influenza. As influenza viruses evolve, seasonal vaccines are updated annually. Within the European project Development of Robust and Innovative Vaccine Effectiveness (DRIVE), a cohort study involving Italian healthcare workers (HCWs) was carried out during the 2018-2019 season. Two aims were defined: to measure influenza vaccine effectiveness (IVE) against laboratory-confirmed influenza cases and to conduct an awareness-raising campaign to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Otherwise, Italy was affected by the SARS-CoV-2 outbreak since mid-February 2020, immediately after the period in which the incidence of influenza-like illness (ILI) gradually increased until reaching the epidemic peak in the fifth week of 2020, with a level equal to about 13 cases per thousand assisted [4]. The complete epidemiological data from 2019/2020 influenza season are not yet available, but we can assume that the aetiology of ILI was similar to that reported for the 2018/ 2019, when about 8 million of cases were registered in Italy and 31.7% caused by influenza viruses [4].…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, Italy was affected by the SARS-CoV-2 outbreak since mid-February 2020, immediately after the period in which the incidence of influenza-like illness (ILI) gradually increased until reaching the epidemic peak in the fifth week of 2020, with a level equal to about 13 cases per thousand assisted [4]. The complete epidemiological data from 2019/2020 influenza season are not yet available, but we can assume that the aetiology of ILI was similar to that reported for the 2018/ 2019, when about 8 million of cases were registered in Italy and 31.7% caused by influenza viruses [4].…”
Section: Dear Editormentioning
confidence: 99%
“…Otherwise, Italy was affected by the SARS-CoV-2 outbreak since mid-February 2020, immediately after the period in which the incidence of influenza-like illness (ILI) gradually increased until reaching the epidemic peak in the fifth week of 2020, with a level equal to about 13 cases per thousand assisted [4]. The complete epidemiological data from 2019/2020 influenza season are not yet available, but we can assume that the aetiology of ILI was similar to that reported for the 2018/ 2019, when about 8 million of cases were registered in Italy and 31.7% caused by influenza viruses [4]. In accordance with epidemiological data, we also observed that 63.6% of 190 COVID-19 patients (admitted to Policlinico Umberto I Hospital of Rome, one of the larger teaching Italian COVID-19 Medical Centers in March 2020) reported in their clinical history a recent ILI (1-3 weeks prior to the appearance of COVID-19-related symptoms).…”
Section: Dear Editormentioning
confidence: 99%
“…Similar evidence has been gathered in an Italian setting [ 13 , 14 , 15 , 16 ]. However, recent shreds of evidence relating to the Italian context have shown that specific organizational and educational interventions may have mixed results in ameliorating influenza VC [ 17 , 18 , 19 , 20 ]. Thus, research is important in finding variables useful in designing systematic interventions aimed at implementing HCWs vaccination coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Glatman-Freedman et al analyzed the variation in the vaccine effectiveness (VE) of influenza vaccination in Israel during the 2018/2019 season according to different clades of influenza A (H3N2) virus [ 22 ], and Barbara et al observed a substantial increase of vaccination adherence among HCWs of the Catholic UH of Rome, Italy, due to evidence-based promoting strategies [ 23 ]. Panatto and colleagues, through a case-control test negative design, analyzed the VE of influenza vaccination during the 2018/2019 season in two Italian regions [ 24 ]. Finally, a study on HBV seroprevalence in pediatric and adolescent populations of Tuscany, Italy, found that immunity due to HBV vaccination reduced virus circulation [ 25 ].…”
Section: Manuscripts Included In the Special Issuementioning
confidence: 99%